A Fuzzy Analytic Hierarchy Process (FAHP) application for multi-criteria purchase decisions regarding various brands of motorcycles / Suzanawati Abu Hasan ... [et al.] - Abu Hasan, Suzanawati; Annuar Farish, Nur Atirah; Teoh, Yeong Kin; Mohd Nasir, Diana Sirmayunie; Ariffin, Anas Fathul (UiTM Cawangan Perlis, 2023)
It shows that motorbikes are widely employed as a primary means of transportation for everyday movement despite the hot environment and frequent downpours, as they discovered that a motorcycle was more effective and efficient due to the congestion. Transport is currently becoming highly important to support all human activities. Because different clients place different values on other brands, the study stresses the need to know about the various motorbike manufacturers and models available on the market. By understanding customer preferences and demands, motorcycle dealers can enhance profitability and buyer satisfaction by offering products that meet or exceed expectations in design, price, availability of special offers, and reliability. The Fuzzy Analytical Hierarchy Process is used in this study to choose the top motorcycle brand names and rate the importance of four criteria. The financial features, promotion and types of motorcycles were employed in this study's Analytical Hierarchy Process (AHP) comparison of each motorcycle brand. These criteria are analysed in detail to give buyers essential insights for making well-informed decisions and optimising their daily satisfaction while minimising costs. The findings of this research contribute to the existing knowledge of decision-making methodologies and provide practical implications for motorcycle businesses in Kota Bharu. The outcome demonstrates that, among the scores of possibilities, Honda is the finest brand for people to purchase concerning related criteria is 0.3881, followed by Suzuki (0.3029), Yamaha (0.2615), and Modenas (0.0476). It is also demonstrated by the approach that finances are the most crucial factor to consider before a buyer engages in a motorcycle purchase by having the highest weight score, which is 0.5920, followed by features (0.2439), motorbike kinds (0.1157) and promotions (0.0484).